Application of Ice Gel For Edible Flowers Distribution Packaging of Butterfly Pea - Ulya, Kamila Nikmatul; Darmawati, Emmy; Wulandani, Dyah (Jurnal Keteknikan Pertanian, 2024)
Butterfly pea (Clitoria ternatea) is a popular edible flower in Indonesia that is rich in antioxidants. However, it is perishable and sensitive to temperature changes during storage and transportation. To maintain its quality, the use of ice gel in distribution packaging has been identified as an effective solution. The aim of this study is to determine the optimal positioning of ice gel in two types of distribution packaging, namely styrofoam box and insulated box. The experiment involved cooling 36 grams of flowers per distribution package over 2 hours of simulation using six pieces of ice gel with two different positions. The results showed that ice gel placed in position 2 was able to reduce the temperature inside the packaging more rapidly and maintain the lowest temperature for a longer period compared to ice gel placed in position 1. Therefore, placing ice gel in position 2 is the best option to be applied in the distribution package. Ice gel position 2 can reduce the flower’s temperature from 20°C to 10.7°C in the styrofoam box and from 20 oC to 11°C in the insulated box during simulation.